The Use of Ultrasound Guidance for the Treatment of Raynaud Disease of the Hand With Botulinum Toxin. (June 2020) - Lobb, David C.; Pierce, Jennifer; Perry, Michael; DeGeorge, Brent
Abstract : Background: This study sought to examine the feasibility and effectiveness of the use of ultrasound (US) as a clinical adjunct in the delivery of botulinum toxin for the treatment of Raynaud disease of the hand. Methods: One cadaver hand was injected with a colored simulation material using the current traditional surface anatomy approach, whereas an additional cadaver hand was injected using US guidance. The hands were dissected and areas of distribution of the simulation material were evaluated. Five patients diagnosed with Raynaud disease were treated with botulinum toxin using US guidance and data using the Patient-Reported Outcomes Measurement Information System Upper Extremity were collected. Results: The cadaver hand injected with a colored simulation material using US guidance demonstrated significantly reduced surface area of muscle infiltrated compared with the cadaver hand injected using the traditional surface anatomy approach (16 cm 2 vs 37 cm 2, P < 0.001). All 5 patients treated with botulinum toxin using US guidance reported significant improvement in symptoms and function after injection ( P < 0.05), where zero patients reported intrinsic hand weakness. Conclusions: The use of US significantly improves the accuracy of delivery of a surrogate dye in a cadaver model of Raynaud disease, whereas its use clinically results in at least as effective a treatment as the landmark approach, but with less botulinum toxin required to achieve the clinical effect.